1988
DOI: 10.1042/bj2530553
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of β-elimination and δ-elimination reactions in the repair of DNA containing AP (apurinic/apyrimidinic) sites in mammalian cells

Abstract: Histones and polyamines nick the phosphodiester bond 3' to AP (apurinic/apyrimidinic) sites in DNA by inducing a beta-elimination reaction, which can be followed by delta-elimination. These beta- and delta-elimination reactions might be important for the repair of AP sites in chromatin DNA in either of two ways. In one pathway, after the phosphodiester bond 5' to the AP site has been hydrolysed with an AP endonuclease, the 5'-terminal base-free sugar 5'-phosphate is released by beta-elimination. The one-nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 32 publications
6
73
0
Order By: Relevance
“…The tetrahydrofuran residue has a hydrogen in the place of a hydroxyl group at the 1' position of the natural AP site and is resistant to cleavage by 1-elimination. Several repair-related enzymes, such as AP lyase (formerly called class I AP endonuclease) and dRPase appear to be inactive at a tetrahydrofuran residue (1,6). It is likely that one of these enzymes is essential for DNA polymerase 3-dependent repair.…”
Section: Discussionmentioning
confidence: 99%
“…The tetrahydrofuran residue has a hydrogen in the place of a hydroxyl group at the 1' position of the natural AP site and is resistant to cleavage by 1-elimination. Several repair-related enzymes, such as AP lyase (formerly called class I AP endonuclease) and dRPase appear to be inactive at a tetrahydrofuran residue (1,6). It is likely that one of these enzymes is essential for DNA polymerase 3-dependent repair.…”
Section: Discussionmentioning
confidence: 99%
“…The lysine-rich N-terminal tails of the histones extend from the protein core, making various contacts with the DNA minor groove. The proximity of nucleosomal AP sites to these basic residues is expected to accelerate cleavage of the lesion relative to naked DNA (26)(27)(28). Previously, Povirk showed that the oxidized abasic lesion produced by bleomycin undergoes rapid strand scission when produced in chromatin (27).…”
mentioning
confidence: 99%
“…The effect of polyamines on apurinic/apyrimidinic (AP) DNA has been investigated previously by several investigators [25,20], and the cleavage induced is most probably caused by B-elimination [25,31]. We have compared the efficiency of three different polyamines which share a common structure.…”
Section: Discussionmentioning
confidence: 99%